Analisis Beda Rata-Rata Pengaruh Fraksi Volume Komposit Pada Pengujian Impact Berpenguat Serat Resam Dan Serat Pinang - Dwi Yulian, Naufal; Masdani, Masdani; Pranandita, Nanda (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
Technological developments and advances in the industrial sector have led to the increasing use of metals. This condition causes the availability of metal raw materials to decrease. Overcoming this, the use of composites in the industrial world is a solution. Many composite reinforcing materials use natural fiber materials are often used because they have advantages in strength and stiffness that are higher than other engineering materials. In this study using a factorial experimental method that looks at the effect of the composite ratio (volume fraction) with the use of 2 natural fiber mixtures, namely resam fiber and areca nut on impact strength. This study aims to determine the average difference in each treatment carried out in the impact test. The volume fraction treatment variants used in this study are 25%; 30%; 35% resam fiber and 10% areca nut fiber with a long soaking time of 2% NaOH mixed fiber for 2 hours with the α value used is 5%. It was found that in treatment 1: 2 the average value is different while in the treatment of 2: 3 and 1: 3 the average value of the variables is not different.